Behaviour Of Engineered Cementitious Composite (ECC) Containing Crumb Rubber Particles Subjected To Elevated Temperature - Lee, Yin Yen (Universiti Teknologi PETRONAS, 2018)
The growing amount of the waste tires have raised ever-increasing environmental concern with the development of the automobile industries. Therefore, utilization of crumb rubber in Engineered Cementitious Composite (ECC) has attracted attention in the construction industry. During the elevated temperature, the crumb rubber (CR) melts and creates escape routes for build-up pressure due to moisture and the matrix. This research reports the influence of crumb rubber on the residual compressive strength of ECC and temperature after expose to elevated temperature up to 1000℃. CR-ECC mixes were developed toward utilizing crumb rubber in the percentage of 0%, 1%, 3% and 5%.”